Intention to use online food delivery services in Indonesia: the study on post-movement control order (MCO) period - Lutfi, Ahmad Mustofa; Juhdi, Nurita (Faculty of Economics and Muamalat, USIM, 2023)
Before the COVID-19 pandemic, Indonesians had a habit of eating outside. Then, the shopping pattern of the Indonesian people changed drastically from initially visiting physical stores (offline) to switching to an electronic system (online), especially in ordering online food delivery services during and after the COVID-19 pandemic. However, after the movement control order (MCO) ended and the Covid-19 cases disappeared, people began to leave their homes and eat in restaurants, malls, and cafes again. MCO has ended so is the demand for online food delivery services going to remain in the market or not after the pandemic? Therefore, the study aimed to examine the intention to use online food delivery services in Indonesia during the post MCO period. This study used the Theory of Planned Behavior, and the respondents for this study amounted to 250 respondents. Determination of the number of respondents was by using non-probability sampling with the purposive sampling method. Respondents in this study were people who had purchased online food delivery services at least once. The data analysis method used is the Statistical Package for Social Sciences (SPSS) Version 22.0. The results showed that attitudes, subjective norms, and perceived control positively affected intention to use online food delivery services in Indonesia during the post MCO period, which means that Indonesian people will continue using online food delivery services after the post MCO period. Based on this research, it is suggested for food and beverage business owners to pay more attention in providing the best service to consumers, because they feel that buying food through providers is excellent and valuable. Promotion or discount programs can also be one of the best service alternatives offered by food and beverage business owners so that consumers remain loyal to use online food delivery services.